2007
DOI: 10.1126/science.1137729
|View full text |Cite
|
Sign up to set email alerts
|

Plant Speciation

Abstract: Like the formation of animal species, plant speciation is characterized by the evolution of barriers to genetic exchange between previously interbreeding populations. Prezygotic barriers, which impede mating or fertilization between species, typically contribute more to total reproductive isolation in plants than do postzygotic barriers, in which hybrid offspring are selected against. Adaptive divergence in response to ecological factors such as pollinators and habitat commonly drives the evolution of prezygot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
939
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 996 publications
(960 citation statements)
references
References 62 publications
10
939
1
10
Order By: Relevance
“…So if we generalize the gene dispersal results from P. punctata to these species, it appears that low migration rates may have contributed to allopatric and parapatric speciation in this clade (Cowling and Lombard 2002;Rieseberg and Willis 2007). The relatively low estimates of genetic diVerentiation among populations, in contrast, suggest a mechanism is operating to maintain signiWcant gene migration among populations.…”
Section: Discussionmentioning
confidence: 97%
“…So if we generalize the gene dispersal results from P. punctata to these species, it appears that low migration rates may have contributed to allopatric and parapatric speciation in this clade (Cowling and Lombard 2002;Rieseberg and Willis 2007). The relatively low estimates of genetic diVerentiation among populations, in contrast, suggest a mechanism is operating to maintain signiWcant gene migration among populations.…”
Section: Discussionmentioning
confidence: 97%
“…The recent research about the natural hybrid P. 9 intortusifolius (Du et al 2009) has confirmed the existence of the bidirectional hybridization in natural populations. Traditionally, conspecific pollen was considered to be advantageous in fertilization compared with nonconspecific pollen (Rieseberg and Willis 2007). Such conspecific advantages, however, were not significant in these two Potamogeton species.…”
Section: Absence Of Prezygotic Barriers In Interspecific Crossesmentioning
confidence: 99%
“…Many different mechanisms, such as ecological separation, mating barriers, and inviability or infertility of hybrids, can prevent interspecific hybridization. Prezygotic barriers, which prevent interspecific fertilization, are considered to be more important in plants than postzygotic barriers (Rieseberg and Willis 2007). So we focused on the prezygotic barriers in Potamogeton and tried to explain the high frequency of interspecific hybrids in this genus by critical experimental hybridization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the timing of their onset, reproductive isolation barriers are classified as either pre‐zygotic (e.g., behavioral, mechanical, or gametic isolation) or post‐zygotic (e.g., hybrid sterility or ecological inviability) (Coyne & Orr, 2004). The local maintenance of distinct species usually requires a combination of different types of barriers, and their hierarchical importance is often taxon‐specific (Coyne & Orr, 1998; Rieseberg & Willis, 2007). …”
Section: Introductionmentioning
confidence: 99%